New Strategies for Manipulating Mitochondrial Dynamics in Cancer Therapy - Tolulope Bolarinwa; Opeoluwa Oluwanifemi Akomolafe; Degadwala, Irene Sagay-Omonogor (International Journal of Scientific Research in Chemistry, 2024)
Mitochondrial dynamics, encompassing fission, fusion, biogenesis, and mitophagy, play critical roles in cancer cell survival and proliferation. Targeting these processes has emerged as a promising therapeutic strategy. Current approaches, including mitochondrial-targeted drugs and inhibitors of key regulatory proteins, have shown potential but face limitations such as off-target effects and resistance. Emerging strategies involve innovative techniques like mitochondrial uncouplers, modulation of calcium homeostasis, and nanotechnology-based delivery systems. Future research aims to develop more selective inhibitors, explore the interplay between mitochondrial dynamics and cellular processes, and enhance targeted delivery systems. These advancements hold significant clinical implications, offering more effective and less toxic cancer treatments, improving the efficacy of existing therapies' efficacy, and enabling personalized approaches. Continued exploration of these strategies promises to advance cancer therapy and improve patient outcomes.
Keywords: Mitochondrial Dynamics; Cancer Therapy; Mitochondrial Fission; Mitochondrial Fusion; Targeted Therapy